Experiências promovidas pela universidade pública e sua relevância na formação de um profissional médico com visão integrada: uma narrativa crítico-reflexiva - Santos, Alessa Vitorini (Universidade Federal de São Carlos, 2025)
Public universities are composed of institutions that aim to fulfill the Brazilian Constitution of 1988, providing access to quality education, while also carrying the social role of training professionals with community awareness, capable of contributing to the development of society and reducing social inequalities. Among such institutions is the Federal University of São Carlos (UFSCar), which, by putting into practice what is established by law and fostering an environment of diversity and teaching-research-extension, offers students unique experiences that contribute to shaping integrated and humanized graduates. Within this plural environment, the UFSCar medical program was created, complementing such experiences and enabling the training of physicians with critical thinking and autonomy in learning, through the active methodology known as the Constructivist Spiral. Furthermore, from the beginning, students in the program are integrated into the different levels of care within the Unified Health System (SUS), in a two-way process in which both medical education and the local population benefit. However, for practical training, students receive support from two additional foundations of the program: theory and simulation. Thus, the aim of this work was to analyze each of these themes involving the public university, the UFSCar medical program, and to interweave them with personal experiences, in order to explain how this journey contributes to the training of a physician with an integrated perspective.
Experiences promoted by the public university and their significance in shaping a medical professional with an integrated vision: a critical-reflective narrative
Keywords: Formação médica; Universidade pública; Espiral construtivista; Prática profissional; Narrativa de experiência; Medical education; Public university; Constructivist spiral; Professional practice; Experience narrative; CIENCIAS DA SAUDE::MEDICINA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 3. Saúde e Bem-Estar; 4. Educação de Qualidade